Systemic Barriers to Postpartum Midwifery Visits and Their Effect on Exclusive Breastfeeding in Rural Indonesia - Peny Ariani; Putri Ayu Yessy Ariescha; Dinillah Salsabila Bahar; Jekson Martiar Siahaan; Nurmala Sari (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Postpartum visits by independent midwives play a critical role in initiating and sustaining exclusive breastfeeding. However, operational and institutional barriers may compromise their effectiveness, particularly in semi‑urban and rural settings such as Deli Tua District. This study examined the association between these barriers and exclusive breastfeeding practices among mothers in Deli Tua. A quantitative cross-sectional study was conducted in 2025, involving all independent midwives in the district (n = 85) and a purposive sample of 120 postpartum mothers (1-6 weeks post-delivery). Data were collected using structured questionnaires and analyzed through Chi-Square tests and multivariate logistic regression at a 95% confidence level. Key barriers negatively associated with exclusive breastfeeding included lack of government incentives (OR = 0.23; 95% CI: 0.09-0.61; p = 0.004), excessive workload and fatigue (OR = 0.33; 95% CI: 0.14-0.78; p = 0.013), high operational costs (OR = 0.38; 95% CI: 0.17-0.83; p = 0.015), and limited time for visits (OR = 0.43; 95% CI: 0.19-0.96; p = 0.043). Conversely, institutional support from health centers significantly increased the likelihood of breastfeeding success (OR = 2.01; 95% CI: 1.01-4.01; p = 0.046). Socio-cultural factors such as stigma and customary practices showed no significant association. To enhance the effectiveness of postpartum care and promote exclusive breastfeeding, the study recommends implementing performance-based incentives, reducing workload burdens, providing financial subsidies, and establishing standardized visit-time guidelines. Strengthening cross-sectoral collaboration and resource allocation is essential to improve service delivery and breastfeeding outcomes. Keywords: Exclusive breastfeeding, postpartum care, health system barriers, community midwives, maternal health services